IMMERSIVE NARRATIVES AS PROSOCIAL AGENTS - Dr. Francisco-Julián MARTÍNEZ-CANO; Dra. Begoña IVARS-NICOLÁS; Dr. Richard LACHMAN (Fonseca, Journal of Communication, 2024)
Alongside the rise of the metaverse, immersive technologies are claiming a place in the media ecosystem. The question of the standardization of extended reality technologies (virtual reality, augmented reality, and mixed reality) as consumer media seems to have become irrelevant in a context characterized by the constant evolution of devices, the development of new content, and the expansion of distribution platforms.